El mundo subjetivo de mujeres violentadas por su pareja. - RODRÍGUEZ NAVA, VÍCTOR FEDERICO; CASIQUE CASIQUE, LETICIA; DE JESÚS MUÑOZ TORRES, TERESITA; AREZ AGUIRRE, ALICIA ÁLV (Cultura de los Cuidados, 2026)
Objective: To interpret the lived experiences of the subjective world in women violated by their partner. Methodology: Qualitative study based on the Theory of Communicative Action, carried out with 14 women who attended the Healthy Relationships Workshop implemented by the Secretary of Health of Aguascalientes. A semi-structured interview was applied consisting of 7 questions about the subjective world. Results: 20 codes were obtained that allowed defining the following phenomenon: Acceptance of violence as a lifestyle, without understanding why to allow abuse, which gives rise to feelings of physical, emotional and family self-destruction. Conclusions: Society has built a false cultural equality between men and women; however, the ideology of family unity has prevented women from empowering themselves and deciding their way of life, this is transmitted to their families and they in turn educate women in such a way, so that they accept "life that they had to live".